Expression of SAP1-3 genes in non-albicans Candida isolates in bovine raw milk and human sample - Namvar, Zahra; Sepahy, Abbas Akhavan; Tabatabaei, Robab Rafiei; Sharifynia, Somayeh; Aala, Farzad; Rezaie, Sassan (Folia microbiologica, 2025)
Candida species are now taken as one of the essential opportunistic pathogens in clinical specimens. Although Candida albicans is one of the most essential opportunistic pathogens, non-albicans Candida (NAC) should not be taken for granted because these microorganisms are among the most common pathogens in patients today, leading to diseases, such as candidiasis, gastrointestinal tract infection, and vulvovaginitis. Fungal agents produce secreted aspartic proteinases (SAPs) to penetrate tissues. SAPs facilitate the invasion and colonization of host tissue by rupturing host mucosal membranes. They play an important role in weakening the structural and immunological defense proteins. The aim of this study was to compare the expression of SAP 1-3 genes in NAC isolated from different samples. We isolated the NAC such as Candida parapsilosis (C. parapsilosis), Candida tropicalis (C. tropicalis), Pichia kudriavzevii (P. kudriavzevii), and Nakaseomyces glabrata (N. glabrata) from two different sources of bovine raw milk and human samples. Then, we compared the expression of SAP1, SAP2, and SAP3 genes in both samples by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). The results of gene expression showed that expression of the genes SAP2 and SAP3 was different in C. parapsilosis detected from raw milk and human samples. The expression of SAP2 was significantly decreased in human samples (**p < 0.01), whereas the expression of SAP3 was significantly increased in human samples (*p < 0.05). In some cases, the expression of these genes was similar among N. glabrata, P. kudriavzevii, and C. tropicalis. The expression of SAP2 and SAP3 genes in the same species of NAC from various sources is different.
Keywords: Non-albicans Candida; Gene expression; SAP; Milk